Plasma-reinforced nonlinear conductive coating and preparation method and application thereof
Through plasma modification and etching technology, the doping ratio and adhesion of the nonlinear conductive coating are optimized, and the problems of mechanical strength reduction and insufficient adhesion of existing coatings are solved, achieving efficient charge regulation and mechanical strength promote.
Patent Information
- Application Number
- CN202411467454.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-21
AI Technical Summary
The existing nonlinear conductive coatings have reduced mechanical strength under high concentration doping, insufficient adhesion, and electric field induction technology is limited in reducing the doping ratio of filler.
The inorganic filler particles and insulating substrates are treated by plasma modification, the compatibility of nonlinear conductive materials and coating substrates is optimized, the doping ratio of nonlinear conductive materials is reduced, and the mechanical introduction is carried out through plasma physical etching and chemical etching. Interlocking, physical adsorption, chemical bonding and bonding modes strengthen the adhesion between the coating and the substrate.
It achieves high nonlinear conductivity and high adhesion under low filler doping, improves the mechanical strength and charge regulation capabilities of the coating, and is suitable for high-pressure DC gas insulating equipment.
Smart Images

Figure CN119446620A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field, and in particular to a plasma-enhanced nonlinear conductive coating and a preparation method and application thereof. Background Art
[0002] The phenomenon of charge accumulation on the surface of insulators under DC voltage is a key issue that limits the long-term safe and stable operation of UHV DC gas-insulated equipment. Therefore, finding an effective method to suppress surface charge accumulation is an essential step in improving the design of HV DC gas-solid insulation. Currently, coating the surface of insulators with nonlinear conductive coatings is considered to be a charge suppression method with great engineering application potential.
[0003] However, the engineering application of nonlinear conductivity coatings still has the following problems. First, the effectiveness of the nonlinear conductivity characteristics of the coating generally requires the doping of inorganic fillers to above their percolation threshold, but high-concentration doping will not only bring great difficulties to the sample preparation process, but also lead to a decrease in the mechanical strength of the finished coating. In addition, the existing coating construction method still lacks consideration for improving the bonding force, so the basic bonding force between the coating and the insulator is low, and there is a very high risk of falling off during the long-term operation of the equipment.
[0004] Research on adhesion enhancement of nonlinear conductive coatings is still in its infancy. Only some scholars have conducted preliminary explorations using mechanical polishing to improve the surface roughness of insulating substrates, but this is still far from meeting the requirements of engineering applications. In addition, in response to the problem of excessive filler ratio in nonlinear conductive coatings, some scholars in this field have proposed using electric field-induced inorganic filler movement to form various anisotropic functional materials, so that the dielectric and physical and chemical properties of the prepared materials are gradiently distributed along the induced electric field direction. This reduces the filler doping ratio under the percolation threshold to a certain extent, and has better charge regulation effect than coatings with uniformly dispersed fillers at the same doping concentration. However, lower filler concentrations often require higher in-situ electric fields to drive the particles into chains, and higher in-situ electric fields will cause the coating matrix to fluctuate violently due to complex electrohydrodynamics, destroying the particle chain structure. Therefore, the current coatings prepared based on electric field induction technology have very limited ability to reduce the particle doping ratio.
[0005] In summary, in order to promote the application of surface coating in DC gas insulation equipment, it is necessary to propose a method for preparing a nonlinear conductive coating with low filler doping and high adhesion. Summary of the invention
[0006] In order to solve the problems existing in the prior art, the present invention uses plasma modification to treat inorganic filler particles and / or the surface of the insulating substrate. On the one hand, the chaining process of the electric field-induced nonlinear conductive material movement is optimized by improving the compatibility between the nonlinear conductive material and the coating matrix, and the doping ratio of the nonlinear conductive material that can stably form a chain is further reduced. On the other hand, the plasma is used to perform physical etching and chemical etching on the surface of the insulating substrate to simultaneously introduce three bonding modes of mechanical interlocking, physical adsorption, and chemical bonding to the coating-substrate bonding interface, so as to achieve the enhancement of the basic adhesion of the coating.
[0007] In order to achieve the above object, the present invention provides a method for preparing a plasma-enhanced nonlinear conductive coating, comprising: The composite coating is applied to the surface of the insulating substrate, and then cured under the action of an electric field to obtain a coating; The composite coating comprises a nonlinear conductive material and a coating matrix; Wherein, the nonlinear conductive material and / or the insulating substrate is / are subjected to plasma treatment.
[0008] Further, the plasma treatment includes: After purging for 1-10 minutes in a mixed gas of oxygen and / or argon at a gas flow rate of 100-200 mL / min, dielectric barrier discharge is used for treatment at a voltage peak of 1-10 kV for 1-10 minutes.
[0009] Preferably, the dielectric barrier discharge uses parallel plate electrodes; the type of blocking medium is quartz glass; the dielectric blocking method can be one of high-voltage electrode blocking, ground electrode blocking, and high-voltage electrode-ground electrode double blocking; the discharge process is driven by a high-voltage power supply, and the power supply waveform is one of high-frequency AC, microsecond pulse, and nanosecond pulse.
[0010] Furthermore, the nonlinear conductive material is subjected to a silanization treatment before the plasma treatment.
[0011] It should be noted that the silanization treatment of the present invention is a conventional operation in the art, which is to use a silane coupling agent to perform surface treatment on a nonlinear conductive material. The type of silane coupling agent does not need to be strictly limited, and can be at least one of KH501, KH550, KH560, KH580, KH602, etc.; the amount of the silane coupling agent is preferably 0.2%-1%; the dispersion solvent of the nonlinear conductive material and the silane coupling agent can be at least one of water, ethanol, acetone, etc. After coupling drying, there may be agglomeration. Preferably, the agglomerated particles are also ball-milled to ensure that the particle size meets the requirements.
[0012] Furthermore, the insulating substrate is surface cleaned before the plasma treatment. The material of the insulating substrate does not need to be strictly limited, and is preferably an epoxy resin or an epoxy-based composite material. The specific cleaning process can be to immerse the insulating substrate in ethanol, ultrasonically clean it for 30-60 minutes at a temperature of 40-60°C and an ultrasonic power of 100-400W, and after cleaning, take out the insulating substrate and dry it in a constant temperature oven with a humidity of 20%RH for 24-72 hours.
[0013] Furthermore, the particle size of the nonlinear conductive material is 5-100 μm. There is no need to strictly limit the type of the nonlinear conductive material, and it can preferably be at least one of silicon carbide and zinc oxide.
[0014] Furthermore, the coating matrix includes coating, curing agent and accelerator.
[0015] Preferably, the preparation process of the composite coating follows the operating principle of the homogeneous material blending method, the timing of mixing the nonlinear conductive material into the coating should be prior to the introduction of the curing agent, the operating temperature of the entire blending process is controlled at 65-75°C, and after the raw materials are blended and prepared, the composite coating is placed at 65°C, and vacuumed while stirring in the environment for 30-60 minutes. After the vacuuming is completed, the composite coating is placed in an environment of 65-75°C for insulation and standby use. The time to complete the preparation of the entire composite coating does not exceed 5 hours.
[0016] In the present invention, the type of coating does not need to be strictly limited, and can be epoxy resin, polyester resin, silicone rubber, etc. Correspondingly, the curing agent and accelerator are selected as suitable types. The ratio of coating, curing agent and accelerator is adjusted as needed and does not need to be strictly limited.
[0017] In the present invention, the amount of nonlinear conductive material added does not need to be strictly limited, and the amount of addition can be set according to the needs of the specific coating, but it should be noted that adding too much may cause the adhesion and stability of the coating to decrease. Optionally, the mass of the nonlinear conductive material is 1-10% of the mass of the coating matrix.
[0018] Furthermore, the parameters of the induction treatment are temperature 80-120°C, voltage amplitude 0.1-1 kV, frequency 100-1000 Hz, and time 2-12 h.
[0019] Furthermore, the curing adopts a step-by-step temperature rise curing. Preferably, it can be a 2-step or 3-step curing, wherein the 2-step curing is: 90°C for 2 hours and then transferred to 110°C for 10 hours; the 3-step curing is: 90°C for 2 hours and then transferred to 100°C for 4 hours and finally transferred to 110°C for 6 hours.
[0020] The present invention also provides a plasma-enhanced nonlinear conductive coating, which is obtained by the above-mentioned preparation method.
[0021] The present invention also provides the use of the plasma enhanced nonlinear conductive coating in direct current gas insulation equipment.
[0022] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention improves the electric field induction method and proposes for the first time to use plasma treatment to optimize the motion chaining process of nonlinear conductive materials under the action of electric field induction, so that nonlinear conductive materials can obtain better nonlinear conductive properties at a lower doping amount.
[0023] (2) The present invention proposes for the first time to use plasma modification treatment to optimize the bonding process between the nonlinear conductive coating and the insulating substrate. The impact of high-energy plasma particles can simultaneously introduce three bonding effects, namely mechanical interlocking, physical adsorption, and chemical bonding, on the surface of the coating and the insulating substrate, thereby enhancing the adhesion of the coating to the surface of the insulating substrate.
[0024] (3) The present invention enables the coating to achieve the actual effect of high nonlinear conductivity and high-strength bonding without using special chemical reagents. The processing method is simple, environmentally friendly and does not affect the formulation system of the coating itself.
[0025] (4) The coating obtained by the present invention has excellent charge and electric field control capabilities, and its DC surface tolerance is better than that of existing coatings. The characteristics of low-doped fillers also ensure the excellent mechanical strength of the coating body, taking into account the functional effectiveness and structural effectiveness of the coating, and has great application potential in high-voltage DC gas insulation equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 A flow chart showing a method for preparing a plasma-enhanced nonlinear conductive coating according to an embodiment of the present invention is shown; Figure 2 The conductivity characteristic diagrams of the coatings prepared in Example 1, Comparative Example 2, and Comparative Example 3 are shown; Figure 3 The graph shows the charge accumulation on the coating surface of the coatings prepared in Example 1, Comparative Example 2 and Comparative Example 3 during the 2h pressurization process; Figure 4 The DC surface flashover voltage result diagram of the coatings prepared in Example 1, Comparative Example 2 and Comparative Example 3 is shown; Figure 5 The adhesion test results of Examples 1-3 and Comparative Example 1 are shown. DETAILED DESCRIPTION
[0028] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0029] The following will be combined with the specific embodiments of the present invention and the drawings of the specification to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1 like Figure 1 As shown, a method for preparing a plasma-enhanced nonlinear conductive coating comprises the following steps: ① Plasma treatment of nonlinear conductive materials: 1) Disperse β-silicon carbide with a particle size of 5 μm and KH550 in ethanol, and then stir for 25 minutes at 25°C and an ultrasonic power of 200 W, wherein the mass of KH550 is 0.5% of the mass of β-silicon carbide. After stirring, a mixed system is obtained, which is transferred to a heating box and dried for 12 hours at a drying temperature of 100°C. After drying, the agglomerated sample is taken out and ground in a ball mill to obtain 5 μm silane-coupled β-silicon carbide, which is transferred to a plasma discharge chamber. The plasma discharge chamber is a transparent device covered with quartz glass on the top and bottom, and the chamber size is 20 cm in diameter and 5 cm in thickness.
[0031] 2) A mixed gas of oxygen and argon was selected as the background gas for plasma treatment. First, a gas washing process was carried out inside the chamber. The gas washing process was completed using a DC flow controller with a flow ratio of oxygen to argon of 1:9. The process lasted for 5 minutes and the total gas flow was maintained at 100 mL / min.
[0032] 3) Turn on the high-frequency sinusoidal AC power supply to start plasma treatment, using dielectric barrier discharge (DBD) and parallel plate electrodes; the barrier medium is quartz glass; the dielectric barrier method is high-voltage electrode-ground electrode double barrier, the power frequency is set to 10kHz, the voltage peak is set to 5kV, and the treatment time lasts for 5min. After the plasma treatment is completed, transfer to a beaker for standby.
[0033] ② Plasma treatment of insulating substrates: 1) The insulating substrate is selected as a sheet insulating sample of alumina / epoxy resin. The insulating substrate is first cleaned, that is, ultrasonic oscillation pretreatment. Specifically, the insulating substrate is placed in a beaker filled with alcohol, and the beaker is placed in a water bath of an ultrasonic disperser to start ultrasonic cleaning. The cleaning power is 150W, the treatment time is 30min, and the cleaning temperature is 45°C. After the treatment, the insulating substrate is taken out of the alcohol and placed in a constant temperature oven for drying. The temperature of the constant temperature oven is set to 60°C, the humidity of the constant temperature oven is controlled to 20%RH, and the drying time is 36h.
[0034] 2) The insulating substrate pretreated by ultrasonic oscillation was transferred to the plasma discharge chamber, and a mixed gas of oxygen and argon was selected as the background gas for plasma treatment. The gas washing process inside the chamber was first carried out. The gas washing process was completed by a DC flow controller with a flow ratio of oxygen to argon of 1:9. The process lasted for 5 minutes and the total gas flow was maintained at 100 mL / min.
[0035] 3) Turn on the high-frequency sinusoidal AC power supply to start plasma treatment, using dielectric barrier discharge and parallel plate electrodes; the barrier medium is quartz glass; the dielectric barrier method is high-voltage electrode-ground electrode double barrier, the power frequency is set to 10kHz, the voltage peak is set to 5kV, and the treatment time lasts for 5 minutes. After the plasma treatment is completed, transfer it to a room temperature cabinet for storage.
[0036] ③Coating raw material blending and in-situ electric field induction: 1) Take E51 epoxy resin and heat it to 100℃ to reduce the viscosity, add the plasma-treated silane-coupled β-silicon carbide obtained in step ① to the E51 epoxy resin, then cool it to 65℃ and stir it for 1h; after stirring, add the curing agent methyl hexahydrophthalic anhydride, continue stirring at 65℃ for 2h, then add the accelerator phenol, and stir and blend at 65℃ for 1h; finally, transfer it to a vacuum oven and evacuate it for 1h to obtain a composite coating, and place it in a constant temperature oven at 65℃ for standby use. Among them, the mass of silane-coupled β-silicon carbide is 5% of the mass of the composite coating, and the mass ratio of E51 epoxy resin, methyl hexahydrophthalic anhydride and phenol is 100:80:0.5.
[0037] 2) In order to adapt to the structure of the flaky alumina / epoxy resin insulating substrate, a self-designed assembly structure is adopted. The assembly structure includes an upper insulating plate, a lower insulating plate and a fixing part. The upper insulating plate and the lower insulating plate are both provided with grooves, electrode reserved grooves and fixing holes. When the upper insulating plate and the lower insulating plate are assembled, the insulating substrate can be confined in the groove and a coating space can be reserved. The groove of the upper insulating plate is also provided with an injection hole for injecting composite coating into the coating space, and the electrode reserved groove is used to install the patch electrode. In this embodiment, the materials of the upper insulating plate and the lower insulating plate are the same, both of which are peek insulating plates. After the insulating substrate after plasma treatment is placed in the assembly structure, it is fixed with a fixing part, and the composite coating is injected through the injection hole. After the composite coating is injected, the patch electrode is set up in the electrode reserved groove and connected to a power supply, which can generate a high-frequency sinusoidal AC power supply.
[0038] 3) Turn on the power supply and conduct in-situ electric field induction at a temperature of 90°C, a voltage amplitude of 500V, and a frequency of 1000Hz for 2 hours.
[0039] ④Step-by-step high temperature curing After the in-situ electric field induction is completed, the assembly structure system with the coating is transferred to a constant temperature oven and set to a two-stage step curing, at 90°C for 2 hours and then at 110°C for 10 hours.
[0040] After completing the above steps, the insulating substrate is taken out from the assembly structure, and a plasma-enhanced nonlinear conductive coating is formed on the surface of the insulating substrate.
[0041] Example 2 It is basically the same as the embodiment, except that: in the insulating substrate plasma treatment in step ②, the plasma treatment time of the insulating substrate is 2 minutes.
[0042] Example 3 Basically the same as in Example 2, except that: the plasma treatment time of the insulating substrate in the insulating substrate plasma treatment step ② is 3min. Comparative Example 1 It is basically the same as the embodiment, except that: in the insulating substrate plasma treatment in step ②, the plasma treatment time of the insulating substrate is 0 min.
[0043] Comparative Example 2 A method for preparing a nonlinear conductive coating, comprising the following steps: ①Silane coupling nonlinear conductivity materials: β-SiC with a particle size of 5 μm and KH550 were dispersed in ethanol, and then stirred for 25 min at 25°C and an ultrasonic power of 200 W, wherein the mass of KH550 was 0.5% of the mass of β-SiC. After stirring, a mixed system was obtained, which was transferred to a heating box and dried for 12 h at a drying temperature of 100°C. After drying, the agglomerated sample was taken out and ground in a ball mill to obtain 5 μm silane-coupled β-SiC.
[0044] ②Prepare coating raw materials Take E51 epoxy resin and heat it to 100℃ to reduce the viscosity, add the silane-coupled β-silicon carbide obtained in step ① to the E51 epoxy resin, then cool it to 65℃ and stir it for 1h; after stirring, add the curing agent methyl hexahydrophthalic anhydride, continue stirring at 65℃ for 2h, add the accelerator phenol, and stir and blend at 65℃ for 1h; finally, transfer it to a vacuum oven and evacuate it for 1h to obtain a composite coating, and place it in a constant temperature oven at 65℃ for standby use. Among them, the mass of silane-coupled β-silicon carbide is 5% of the mass of the composite coating, and the mass ratio of E51 epoxy resin, methyl hexahydrophthalic anhydride and phenol is 100:80:0.5.
[0045] ③Step-by-step high temperature curing The selection and cleaning method of the insulating substrate are the same as those in Example 1 and will not be described again. The composite coating obtained in step ② is applied to the surface of the insulating substrate, and then transferred to a constant temperature oven, which is set to a two-stage step curing, at 90°C for 2 hours and then at 110°C for 10 hours, to form a nonlinear conductive coating on the surface of the insulating substrate.
[0046] The thickness of the coating formed in Comparative Example 1 and Example 1 is the same.
[0047] Comparative Example 3 A method for preparing an in-situ electric field induced nonlinear conductive coating, comprising the following steps: ①Silane coupling nonlinear conductivity materials: β-SiC with a particle size of 5 μm and KH550 were dispersed in ethanol, and then stirred for 25 min at 25°C and an ultrasonic power of 200 W, wherein the mass of KH550 was 0.5% of the mass of β-SiC. After stirring, a mixed system was obtained, which was transferred to a heating box and dried for 12 h at a drying temperature of 100°C. After drying, the agglomerated sample was taken out and ground in a ball mill to obtain 5 μm silane-coupled β-SiC.
[0048] ②Prepare coating raw materials Take E51 epoxy resin and heat it to 100℃ to reduce the viscosity, add the silane-coupled β-silicon carbide obtained in step ① to the E51 epoxy resin, then cool it to 65℃ and stir it for 1h; after stirring, add the curing agent methyl hexahydrophthalic anhydride, continue stirring at 65℃ for 2h, add the accelerator phenol, and stir and blend at 65℃ for 1h; finally, transfer it to a vacuum oven and evacuate it for 1h to obtain a composite coating, and place it in a constant temperature oven at 65℃ for standby use. Among them, the mass of silane-coupled β-silicon carbide is 5% of the mass of the composite coating, and the mass ratio of E51 epoxy resin, methyl hexahydrophthalic anhydride and phenol is 100:80:0.5.
[0049] ③ In-situ electric field induction and step-by-step high temperature curing 1) The selection and cleaning method of the insulating substrate are the same as in Example 1, which will not be described in detail here. Because an electric field needs to be applied, the same assembly structure as in Example 1 is adopted. Please refer to Example 1 for the specific structure, which will not be described in detail here. After the composite coating obtained in step ② is injected, a patch electrode is set up in the electrode reserved groove, and the power supply is connected and turned on to perform in-situ electric field induction at a temperature of 90°C, a voltage amplitude of 500V, and a frequency of 1000Hz for 2 hours.
[0050] 2) After the in-situ electric field induction is completed, the assembly structure system with the coating is transferred to a constant temperature oven and set to a two-stage step curing, which is continued at 90°C for 2 hours and then transferred to 110°C for 10 hours. The insulating substrate is removed from the assembly structure, and a nonlinear conductive coating is formed on the surface of the insulating substrate.
[0051] Test Case The conductivity of nonlinear conductive coatings under high voltage is particularly important for their performance. The conductivity characteristics of the coatings prepared in the embodiments and comparative examples were tested. The results are as follows: Figure 2 As shown. Figure 2 It can be seen that the conductivity of the nonlinear conductive coating of Comparative Example 2 is not significantly improved under the condition of an electric field strength of 1-10 kV / m, which may be caused by the fact that the amount of the nonlinear conductive material silane-coupled β-silicon carbide added is too small; while Comparative Example 3, which is subjected to in-situ electric field induction, exhibits relatively obvious nonlinear conductivity characteristics under electric field changes, because the application of an alternating electric field causes the silane-coupled β-silicon carbide to be arranged into chains along the electric field direction, and the resulting coating exhibits good nonlinear conductivity characteristics at a lower doping concentration. However, Example 1, which is subjected to plasma enhancement and in-situ electric field induction, exhibits significant nonlinear conductivity characteristics under electric field changes, because plasma enhancement optimizes the movement chaining process of silane-coupled β-silicon carbide under electric field induction, and optimizes the bonding process between the nonlinear conductive coating and the base insulating substrate.
[0052] The coatings of the examples and comparative examples were pressurized at a voltage of +15 kV for 2 h, and the charge accumulation on the coating surface was recorded. The results are as follows: Figure 3 As shown. Figure 3 It can be seen that the plasma enhanced nonlinear conductive coating prepared in Example 1 exhibits minimal surface charge accumulation performance during the pressurized period, which is due to the better arrangement of the β-silicon carbide particles.
[0053] The DC surface flashover voltage of the coatings of the embodiment and the comparative example was tested, and the results are as follows: Figure 4 It can be seen that compared with direct coating preparation, the coating prepared by in-situ electric field induction and plasma enhancement and in-situ electric field induction has a higher flashover voltage.
[0054] The adhesion of the coatings prepared under different plasma treatment times on the insulating substrate was also tested. Figure 5 As shown. It can be seen that compared with the comparative example 1 without plasma treatment, the adhesion strength of the examples 1-3 after plasma treatment is significantly increased, and shows an upward trend over time. This is because the plasma modification treatment optimizes the bonding process between the nonlinear conductive coating and the insulating substrate. The impact of the plasma high-energy particles can simultaneously introduce three bonding effects of mechanical interlocking, physical adsorption, and chemical bonding on the surface of the coating and the insulating substrate, thereby strengthening the adhesion of the coating on the surface of the insulating substrate.
[0055] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a plasma-enhanced nonlinear conductive coating, characterized in that: include, The composite coating is applied to the surface of the insulating substrate, and then cured under the action of an electric field to obtain a coating; The composite coating comprises a nonlinear conductive material and a coating matrix; Wherein, the nonlinear conductive material and / or the insulating substrate is / are subjected to plasma treatment.
2. The method for preparing a plasma enhanced nonlinear conductive coating according to claim 1, characterized in that: The plasma treatment comprises: After purging for 1-10 minutes in a mixed gas of oxygen and / or argon at a gas flow rate of 100-200 mL / min, dielectric barrier discharge is used for treatment at a voltage peak of 1-10 kV for 1-10 minutes.
3. The method for preparing a plasma enhanced nonlinear conductive coating according to claim 1, characterized in that: The nonlinear conductive material is also subjected to a silanization treatment prior to the plasma treatment.
4. The method for preparing a plasma enhanced nonlinear conductive coating according to claim 1, characterized in that: The insulating substrate is also surface cleaned before plasma treatment.
5. The method for preparing a plasma enhanced nonlinear conductive coating according to claim 1, characterized in that: The particle size of the nonlinear conductive material is 5-100 μm.
6. The method for preparing a plasma enhanced nonlinear conductive coating according to claim 1, characterized in that: The coating matrix comprises coating, curing agent and accelerator.
7. The method for preparing a plasma enhanced nonlinear conductive coating according to claim 1, characterized in that: The parameters of the induction treatment are temperature 80-120° C., voltage amplitude 0.1-1 kV, frequency 100-1000 Hz, and time 2-12 h.
8. A plasma enhanced nonlinear conductive coating, characterized in that: The method is obtained by the preparation method according to any one of claims 1 to 7.
9. Use of the plasma enhanced nonlinear conductive coating according to claim 8 in direct current gas insulation equipment.
Citation Information
Patent Citations
Method and device for preparing high-conductivity nonlinear coefficient coating induced by in-situ electric field
CN117116576A
Plasma-based self-assembly nonlinear conductive coating preparation system and method
CN119419008A
Cited By
Phase change material shaping and cold packaging method based on high polymer material crosslinking
CN120137236A
A method for shaping and cold encapsulating phase change materials based on polymer crosslinking
CN120137236B